2010
DOI: 10.1021/ac1013767
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Detection of Silver in the Low ppt Range with Ion-Selective Electrodes Based on Ionophore-Doped Fluorous Membranes

Abstract: Ionophore-doped sensing membranes exhibit greater selectivities and wider measuring ranges if their membrane matrixes are noncoordinating and solvate interfering ions poorly. This is particularly true for fluorous phases, which are the least polar and polarizable condensed phases known. In this work, fluorous membrane matrixes were used to prepare silver ion-selective electrodes (ISEs). Sensing membranes composed of perfluoroperhydrophenanthrene, sodium tetrakis[3,5-bis(perfluorohexyl)phenyl]borate, and one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 47 publications
(121 reference statements)
1
69
0
Order By: Relevance
“…5,6 Such membrane materials reject hydrophilic and hydrophobic species and represent an important new direction in ion sensor development.…”
mentioning
confidence: 99%
“…5,6 Such membrane materials reject hydrophilic and hydrophobic species and represent an important new direction in ion sensor development.…”
mentioning
confidence: 99%
“…It has also been found that silver is toxic to humans at a concentration as high as 97.2 µg L -1 in drinking water. [7][8][9][10] On the other hand, owing to the fact that Ag + has moderate coordination ability, it is quite difficult to be discriminated from other chemically similar toxic elements. Therefore, separation and recovery of silver from waste and industrial sources are environmentally and economic important.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, about 2500 tons of silver are released into the environment annually, and approximately 80 tons end up in surface waters (Ratte 1999;Mashhadizadeh et al 2013). Silver is not as toxic to humans as many other heavy metals, but the U.S. Environmental Protection Agency reported that a concentration higher than 1.6 nM is toxic to fish and microorganisms (Lai et al 2010) and the maximum contaminant level for total silver in drinking water was set to 0.9 lM, according to the Environmental Protection Agency in Washington DC of USA (1991).…”
Section: Introductionmentioning
confidence: 99%